1992
DOI: 10.1038/hdy.1992.141
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinism of the cellular immune reaction in Drosophila melanogaster

Abstract: Larvae of Drosophila melanogaster produce a haemocytic reaction against eggs of the parasitoid Leptopilina boulardi, which leads to the formation of a multicellular capsule surrounding the foreign object. Melanization resulting from the conversion of phenol to o-quinones frequently accompanies the cellular reaction. Although various cytological and biochemical aspects of this reaction have been investigated, very little is known about genetic determinism of the insect immune response. The heredity of the capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 32 publications
2
87
0
Order By: Relevance
“…The basis of resistance to parasitism has been investigated using these strains. Results strongly indicate a simple genetic determinism in the case of parasitism by L. boulardi (Carton et al 1992) and Asobara tabida (Benassi et al 1998). The major genes are inherited autosomally, with the resistant phenotype showing complete dominance over the susceptible one.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…The basis of resistance to parasitism has been investigated using these strains. Results strongly indicate a simple genetic determinism in the case of parasitism by L. boulardi (Carton et al 1992) and Asobara tabida (Benassi et al 1998). The major genes are inherited autosomally, with the resistant phenotype showing complete dominance over the susceptible one.…”
Section: Introductionmentioning
confidence: 85%
“…melanogaster resistance against the parasitic wasps L. boulardi and A. tabida is under the control of major genes (Carton et al 1992;Orr & Irving 1997;Benassi et al 1998). These genes, Rlb (resistance to L. boulardi) and Rat (resistance to A. tabida), have been localized on chromosome 2 using chromosome-transfer experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic variation for resistance to parasites has been found in many nonsocial organ-isms (Ebert et al 1998;Carius et al 2001;Little and Ebert 1999Kover and Schaal 2002), and has recently been demonstrated in bumblebees and honeybees (Baer and Schmid-Hempel 2003;Palmer and Oldroyd 2003). Although the mechanism in these latter cases is not yet known, the cellular immune response in insects can vary between genotypes (Carlton et al 1992;Cotter and Wilson 2002). This is thought to contribute to the well-established differences in immune response between bumblebee colonies (König and Schmid-Hempel 1995;Allander and Schmid-Hempel 2000;Mallon et al 2003).…”
Section: Acromyrmex and Pogonomyrmex])mentioning
confidence: 99%